2010
DOI: 10.1107/s1600536810017150
|View full text |Cite
|
Sign up to set email alerts
|

(E)-3-(3-Chlorophenyl)-1-(4-methoxyphenyl)prop-2-en-1-one

Abstract: The title mol­ecule, C16H13ClO2, is trans with respect to the C=C double bond. The dihedral angles between the mean plane of the prop-2-en-1-one unit and those of the 3-chloro- and 4-meth­oxy-substituted benzene rings are 20.93 (9) and 20.42 (10)°, respectively, and the dihedral angle between the mean planes of the two benzene rings is 40.96 (5)°. The crystal structure is stabilized by weak inter­molecular C—H⋯O hydrogen bonds, forming chains along the b axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Similarly, chalcones are the compounds well known for their versatile and diverse nature of biological properties such as anti-tuberculosis, anti-cancer, anti-oxidant, anti-inflammatory, anti-amoebicidal, anti-protozoal, immunosuppressive, anti-bacterial and anti-fungal activities. 17) These also find their Fig. 1.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Similarly, chalcones are the compounds well known for their versatile and diverse nature of biological properties such as anti-tuberculosis, anti-cancer, anti-oxidant, anti-inflammatory, anti-amoebicidal, anti-protozoal, immunosuppressive, anti-bacterial and anti-fungal activities. 17) These also find their Fig. 1.…”
Section: Introductionmentioning
confidence: 65%
“…14) Compounds were obtained by the synergism of nalidixic acid with quanidinyl, acetyl coumarin based chalcones and substituted isatin were found effective against Staphylococcus aureus, Escherichia coli and mycobacterium strains. 15,16) These studies have opened further ways of derivatizing nalidixic acid to incorporate multifarious medicinal properties to the basic nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…For antiinflammatory chalcones, see: Nowakowska (2007). For related structures, see: Ahmad et al(2010); Arai et al(1994); Jasinski et al (2010); Li et al (1992); Patil et al (2007); Shettigar et al (2006). For standard bond lengths, see; Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%
“…The synthesis and biological evaluation of simple methoxylated chalcones as anticancer, anti-inflammatory and antioxidant agents is recently reported (Bandgar et al, 2010). The crystal structures of some related chalcones containing methoxy substituents, viz., 4-bromo-4′-methoxy-chalcone (Li et al, 1992), 4-bromo-4′-methoxychalcone (Arai et al, 1994), 1-(4bromophenyl)-3-(4-methoxyphenyl)prop-2-en-1-one (Shettigar et al, 2006) and 1-(4-bromophenyl)-3-(3-methoxyphenyl) prop-2-en-1-one (Patil et al, 2007), a monoclinic polymorph of 1-(4-chlorophenyl)-3-(4-methoxyphenyl)prop-2en-1-one (Jasinski et al, 2010) and (E)-3-(3-chlorophenyl)-1-(4-methoxyphenyl) prop-2-en-1-one (Ahmad et al, 2010) have been reported. Hence in continuation with the synthesis and crystal structure of chalcones and their derivatives, this new chalcone containing the piperidine moiety was synthesized and its crystal structure is reported herein.…”
Section: S1 Commentmentioning
confidence: 99%